2010
DOI: 10.1590/s0102-311x2010000900004
|View full text |Cite
|
Sign up to set email alerts
|

Impacto do incentivo ao aleitamento materno entre mulheres trabalhadoras formais

Abstract: This study focused on programs to promote breastfeeding in order to prevent early weaning of working mothers ' infant children. A non-randomized O incentivo ao aleitamento materno tem sido o objetivo de diversos grupos de profissionais da saúde, em diferentes localidades do Brasil. Esses grupos relatam índices satisfatórios de adesão das mães a essa prática, mostrando que entre 35% e 38,6% das crianças são mantidas em aleitamento materno exclusivo até o sexto mês de idade 2,3,4 . Índice superior foi relatado… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
31

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(41 citation statements)
references
References 29 publications
0
10
0
31
Order By: Relevance
“…According to a research that assessed the prevalence of BF in the country (Venancio, Escuder, Saldiva, & Giugliani, 2010), the average duration of breastfeeding increased from 296 to 342 days, and from 23.4 to 54.1 days for exclusive breastfeeding (EBF), from 1999 to 2008. However, despite positive data, the progress reported by the research is far from ideal; this fact is influenced by several factors such as beliefs and cultural practices (Brasileiro, Posson, Carrascoza, Ambrosano, & Moraes, 2010).…”
Section: Introductionmentioning
confidence: 90%
“…According to a research that assessed the prevalence of BF in the country (Venancio, Escuder, Saldiva, & Giugliani, 2010), the average duration of breastfeeding increased from 296 to 342 days, and from 23.4 to 54.1 days for exclusive breastfeeding (EBF), from 1999 to 2008. However, despite positive data, the progress reported by the research is far from ideal; this fact is influenced by several factors such as beliefs and cultural practices (Brasileiro, Posson, Carrascoza, Ambrosano, & Moraes, 2010).…”
Section: Introductionmentioning
confidence: 90%
“…Dispor de espaços para a prática da amamentação no ambiente de trabalho é uma estratégia que contribui para sua maior duração (19). Por outro lado, o fato de o empregador não conhecer as leis referentes à mulher que amamenta faz com que não proporcione às mães um local apropriado para ordenha, além de não lhes oferecer condições necessárias para a guarda do filho.…”
Section: Categoria II -Características Da Mãeunclassified
“…This is a worrying situation, as the use of baby bottle is associated to early ablactation. (16,17) Through the identification of the factors associated with early ablactation the multivariate analysis showed that only the variable ethnic group was associated in an independent manner, and the Katukina group presented lower percentage of early ablactation than the others. The chance of occurrence of early ablactation among the Poyanawa, Nawa, and Nukini ethnicities was 3.7 times higher than the values observed for the Katukina ethnicity.…”
Section: Ame -Exclusive Breastfeedingmentioning
confidence: 99%